Analysis of kinematic differences in body kick movements in mixed martial arts athletes with and without chronic low back pain - Lee, K. I.; Lee, D. H. (Korean Journal of Sport Biomechanics, 2023)
Objective: The purpose of this study is to identify the difference in the quality of muscle contraction and kick movements according to the presence or absence of back pain in body kick movements of mixed martial arts athletes. Method: In this study, four athletes (32.75 ± 4.79 yrs, 172.50 ± 5.20 cm, 77.73 ± 13.28 kg) who have suffered chronic back pain for more than three months and scored 12 points in the Korean version of ODI. Four painless athletes (33.50 ± 4.04 yrs, 174.25 ± 3.10 cm, 83.50 ± 10.21 kg) participated. Results: During the body kick operation, the pain group had significantly higher muscle activity in the right Transversus abdominis and right Rectus femoris compared to the normal group (p<.05). In the rectus abdominis, the muscle activity was significantly lower than that of the normal group (p<.05). Also, the pain group has a higher toe speed than the normal group Significantly slow (p<.05), there was a delay in contraction of the Transversus abdominis. Conclusion: The results of this study suggest that chronic pain in the lumbar spine degrades the core's function, resulting in inefficient coordination such as Transversus abdominis contraction delay and Transversus abdominis and Rectus femoris excessive activation to compensate for it.